An overview of prospects and challenges in the field of climate change in Malaysia - Al-Amin, A.Q. (2011)
Malaysia is realising the consequence of climate change impacts and efforts are harmonising with those of national interests. Here, we explain recent climate change experiences, several framework structures for policies and national agendas on climate change concerns undertaken in Malaysia. We attempt to identify three areas of policy concerns (a) issues (b) impacts and (c)strategies and figure out the national challenge: i incorporating development concerns into climate policy ii incorporating climate concerns into development policy. We also evaluate ongoing policy preparations and strategies on climate change issues, and provide a critical review to improve Malaysian climate change related initiatives